2003
DOI: 10.7249/dru3041
|View full text |Cite
|
Sign up to set email alerts
|

Los Angeles County Young Children’s Literacy Experiences, Emotional Well-Being and Skills Acquisition: Results from the Los Angeles Family and Neighborhood Survey

Abstract: The RAND unrestricted draft series is intended to transmit preliminary results of RAND research. Unrestricted drafts have not been formally reviewed or edited. The views and conclusions expressed are tentative. A draft should not be cited or quoted without permission of the author, unless the preface grants such permission. RAND is a nonprofit institution that helps improve policy and decisionmaking through research and analysis. RAND's publications and drafts do not necessarily reflect the opinions or policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Neighborhood cohesion. Neighborhood cohesion was assessed using items adapted from the Los Angeles Family and Neighborhood Survey (Lara-Cinisomo & Pebley, 2003). Parental perceptions regarding neighborhood cohesion were measured during the first two waves with 10 items (e.g., "This is a close-knit neighborhood that is cohesive and unified").…”
Section: Methodsmentioning
confidence: 99%
“…Neighborhood cohesion. Neighborhood cohesion was assessed using items adapted from the Los Angeles Family and Neighborhood Survey (Lara-Cinisomo & Pebley, 2003). Parental perceptions regarding neighborhood cohesion were measured during the first two waves with 10 items (e.g., "This is a close-knit neighborhood that is cohesive and unified").…”
Section: Methodsmentioning
confidence: 99%
“…This means that poor children who were cared for exclusively by their parents were more likely, on average, to have poorly educated mothers. Results from our earlier analyses of L.A.FANS showed that more poorly educated mothers are less likely to read to their children, to have books in the household, and to provide other important early learning experiences (Lara-Cinisomo and Pebley, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Children who live in poverty and whose parents are poorly educated are particularly vulnerable to behavior problems and delayed development of basic skills (Brooks-Gunn and Duncan, 1997;Bradley and Corwyn, 2002). Part of the reason may be the quality of the home environment: In an earlier report on Los Angeles County, we showed that poor maternal education and living in poor neighborhoods made it less likely that children were read to or visited the library regularly (Lara-Cinisomo and Pebley, 2003).…”
Section: Chapter One Introductionmentioning
confidence: 84%
“…FANS shows that ethnicity and immigrant status are not important predictors of school readiness, once differences in socioeconomic status are taken into account. In fact, when socioeconomic status is taken into account, children whose parents were born outside the United States do better on basic skills than children with U.S.‐born parents 33 …”
Section: Children In Immigrant Familiesmentioning
confidence: 99%
“…In fact, when socioeconomic status is taken into account, children whose parents were born outside the United States do better on basic skills than children with U.S.-born parents. 33 Glick and White find that when family characteristics are taken into account, school achievement gains of immigrant high schoolers equal or exceed those of their native peers. Family characteristics-parents' income and education, race/ethnicity, and language-had a greater impact on achievement levels and gains than the length of time a student lived in the United States.…”
Section: Children In Immigrant Familiesmentioning
confidence: 99%